Money Politics in Indonesian Democratic Practices - Holish, Amarru Muftie; Rohmat, Rohmat; Syarifudin, Iqbal (Law Research Review Quarterly, 2018)
Democracy is a system of government that is considered modern in the twentieth century. Along with the development of the situation, the system of government in the world of democracy has existed together with the monarchy as a familiar system of government. Montesque's theory of division Trias politics is to be very easily implemented with a democratic system. Indonesia as one of the modern countries in the world that also implements the Pancasila Democracy system in its government system as one of the 4th largest countries in the world that adheres to the Indonesian democratic system has become a role model in the democratic system. The selection of regional heads autonomously and direct presidential elections is a golden achievement of Indonesia's democratic system, coupled with several regional head elections that have been carried out simultaneously making Indonesia increasingly establish itself as a modern with a democratic system. However, the democratic system also has a number of weaknesses, one of which is financial matters that require high costs, so that democracy often causes problems in the financial sector because it requires a lot of money in the event. Not infrequently the practice of money politics takes place in the practice of democracy so that everything really hurts the essence of the state, then what is the legal view of Indonesia regarding money politics in democracy then what are the sanctions for perpetrators of money politics in the perspective of criminal law in Indonesia.